Collectie Vlaamse Gemeenschap aanwinsten 1999-2001. - Brams, Koen; Cornelis, Jef; Pültau, Dirk; Feys, Hans; Shields, Mari; Wouters-Smets, Brigitte; Van Rooij, Jopie (Brussel : Vlaams Ministerie van Cultuur, Jeugd, Sport en Media Brussel, 2005)
't Jolle, Sven ; Allart, Jeroen ; Balkenhol, Stephan ; de Beeck, Hans Op ; Bervoets, Fred ; Blank, Martin ; Van Bossche, Guy ; Braeckman, Dirk ; Broucke, Koen ; Brouwn, Stanley ; De Bruyckere, Berlinde ; Buylen, Michel ; Bytebier, Jean-Marie ; Cingolani, Marco ; Claerbout, David ; Creten, Johan ; De Cupere, Peter ; d'O, Honoré ; Daems, Anne ; Delrue, Ronny ; Denmark ; Devriendt, Robert ; Diamond, Jessica ; Dieleman, Piet ; Dona, Lydia ; Droste, Monika ; Dujourie, Lili ; Fabre, Jan ; Frize, Bernard ; Gentils, Vic ; Geys, Jef ; Gillen, Tina ; Hadzifejzovic, Jusuf ; Heylen, Jan ; Heyvaert, René ; Horowitz, Jonathan ; Huang Yong Ping ; Huisman, Michel ; Huyghe, Philip ; Van Isacker, Philip ; Jacobs, Henri ; Judd, Donald ; Kabakov, Ilya ; Kasimir, Marin ; Kempenaers, Jan ; Van Kerckhoven, Anne-Mie ; Leroy, Eugène ; Macchi, Jorge ; Manders, Mark ; Matthys, Danny ; McCollum, Allan ; Mees, Guy ; Mortier, Antoine ; Mouffe, Michel ; van Oost, Jan ; Otto, Peter ; Pacquée, Ria ; Renard, Thierry ; Robijns, Gert ; Rogiers, Peter ; Rombouts, Guy ; Sack, Stephen ; Sedmach, Manuela ; Serse ; De Smet, Gery ; Strik, Elly ; Swennen, Walter ; Tuymans, Luc ; Uslé, Juan ; Vandenberg, Philippe ; Vanderleenen, Marc ; Vandevelde, Ludwig ; Vari, Minnette ; de Ven, Lidwien van ; Vercruysse, Jan ; Verduyn, Jacques ; Verhoeven, Gert ; Visic, Loreta ; Voordeckers, Jörgen ; de Vos, Eddy ; De Vylder, Paul ; Webb, Boyd ; Zandvliet, Robert
biog., ind. tent., gr. tent., geselect. bibliog. p. 186-398
Engels
Frans
Nederlands
boek